The Development of Travel and Tourism Industry in Iran - Orishev, Aleksandr B.; Mamedov, Azer A.; Zalysin, Igor Yu.; Kotusov, Dmitry V.; Grigoriev, Sergey L. (International Journal of Criminology and Sociology, 2022)
The article presents the results of scientific research devoted to the study of tourism in the countries of the Far East, obtained at one of its stages. The purpose of the article is to characterize the state of rural tourism in Iran. The article shows how the attitude to tourism has changed in this country, uncovering the main reasons for the growth of domestic and international tourist flows in recent years. There are several areas of rural tourism in Iran, which include visits to historical villages and free trade zones, camping in nomad tents, recreation in parks and natural resorts, and trips to the desert. The main research findings of the authors demonstrate the problems facing rural tourism in Iran and identify the risks that arise in this sector of the economy.